2020
DOI: 10.3390/jpm10020047
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Achieving Tacrolimus Target Blood Concentration Might Be Avoided by a Wide Genotyping of Transplanted Patients: Evidence from a Retrospective Study

Abstract: Precise tacrolimus treatment in transplanted patients is achieved in the clinical setting by performing therapeutic drug monitoring (TDM) and consequently adjusting therapy. The aim of this study was to retrospectively analyze the variability in tacrolimus blood levels throughout 2 years of observation in 75 transplanted patients and to investigate if tacrolimus blood levels correlate with presence of genetic polymorphisms, thus modifying tacrolimus pharmacokinetics. CYP3A5*1 (G6986A), CYP3A4*1B (A392G), CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Results showed that the percentage of patients with TAC levels out of therapeutic range was significantly higher in the IM group when compared with the WT or the TM group ( p = 0.001 and p = 0.004). Moreover, an IM pattern resulted, as an independent predictor of number of tacrolimus blood levels out of therapeutic range ( p = 0.015), while RM pattern was inversely related to the TAC administered dose ( p = 0.006) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the percentage of patients with TAC levels out of therapeutic range was significantly higher in the IM group when compared with the WT or the TM group ( p = 0.001 and p = 0.004). Moreover, an IM pattern resulted, as an independent predictor of number of tacrolimus blood levels out of therapeutic range ( p = 0.015), while RM pattern was inversely related to the TAC administered dose ( p = 0.006) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carriers of at least one copy of nucleotide A have *1 allele and are defined CYP3A5 expressers, while homozygotes G/G are *3/*3 and are considered non-expressers [ 11 ] because the substitution of G with A causes an altered mRNA splicing responsible for an early stop codon that produces a non-functional protein [ 12 ]. Therefore, CYP3A5 expressers may have a higher drug-metabolizing ability that could lead to therapeutic failure [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the influence of recipient SLCO1B1 rs2291075 genotype on tacrolimus C/D ratios was confirmed in the slow elimination subgroup, which excluded the interference come from donor and recipient CYP3A5 rs776746. Two studies of renal transplant patients illustrated that SLCO1B1 polymorphisms were associated with tacrolimus concentrations, and genotyping for SLCO1B1 SNPs may be useful for individualized medicine of tacrolimus [ 23 , 24 ]. There are obvious differences in influence factors of tacrolimus elimination between liver transplantation and renal transplantation due to the state of metabolic organ (the liver and intestine), internal environment, and dose required.…”
Section: Discussionmentioning
confidence: 99%
“…Носители хотя бы одной копии нуклеотида А имеют аллель *1 и считаются экспрессирующими CYP3A5, в то время как гомозиготы G/G имеют аллель *3/*3 и считаются неэкспрессирующими [7]. Следовательно, экспрессирующие CYP3A5 могут иметь более высокую способность метаболизировать лекарственные средства [8].…”
Section: Introductionunclassified